Impact of severe acute respiratory syndrome (SARS) on pulmonary function, functional capacity and quality of life in a cohort of survivors. Issue 5 (28th April 2005) - Hui, D S; Joynt, G M; Wong, K T; Gomersall, C D; Li, T S; Antonio, G; Ko, F W; Chan, M C; Chan, D P; Tong, M W; Rainer, T H; Ahuja, A T; et al.
Abstract : Objective: To examine the impact of severe acute respiratory syndrome (SARS) on pulmonary function, exercise capacity, and health-related quality of life (HRQoL) among survivors. Methods: 110 survivors with confirmed SARS were evaluated at the Prince of Wales Hospital, HK at the end of 3 and 6 months after symptom onset. The assessment included lung volumes (TLC, VC, RV, FRC), spirometry (FVC, FEV1 ), carbon monoxide transfer factor (Tlco adjusted for haemoglobin), inspiratory and expiratory respiratory muscle strength (Pimax and Pemax), 6 minute walk distance (6MWD), chest radiographs, and HRQoL by SF-36 questionnaire. Results: There were 44 men and 66 women with a mean (SD) age of 35.6 (9.8) years and body mass index of 23.1 (4.8) kg/m 2 . Seventy (64%) were healthcare workers. At 6 months 33 subjects (30%) had abnormal chest radiographs; four (3.6%), eight (7.4%), and 17 (15.5%) patients had FVC, TLC, and Tlco below 80% of predicted values; and 15 (13.9%) and 24 (22.2%) had Pimax and Pemax values below 80 cm H2 O, respectively. The 6MWD increased from a mean (SD) of 464 (83) m at 3 months to 502 (95) m (95% CI 22 to 54 m, p<0.001), but the results were lower than normal controls in the same age groups. There was impairment of HRQoL at 6 months. Patients who required ICU admission (n = 31) had significantly lower FVC, TLC, and Tlco than those who did not. Conclusion: The exercise capacity and health status of SARS survivors was considerably lower than that of a normal population at 6 months. Significant impairment in surface area for gas exchange was noted in 15.5% of survivors. The functional disability appears out of proportion to the degree of lung function impairment and may be related to additional factors such as muscle deconditioning and steroid myopathy.